2010
DOI: 10.1021/jp1031306
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of Sulfur Adsorption at the (001) Surface of Metal-Rich Nickel Phosphides: Effect of the Ni/P Ratio

Abstract: A significant increase of the sulfur uptake by Ni x P with an increasing Ni to P ratio from 2 to 3 was reported recently in ultradeep adsorption desulfurization (ADS) of diesel fuel. It corresponded to increased Ni x P surface coverage, while no bulk Ni−P−S phases were identified. Density functional theory is applied in this communication to calculate the adsorption energies for S adatoms adsorbed on the surface of Ni2P, Ni12P5, and Ni3P phases. The preferable (001) surface-terminated slabs are considered to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Moreover, the magnitude of the DOS at E f serves as indicator for the ability to form bonds with adsorbed species. 27 The DOS for the other surfaces can be seen in Fig. S16–S19 in the ESI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the magnitude of the DOS at E f serves as indicator for the ability to form bonds with adsorbed species. 27 The DOS for the other surfaces can be seen in Fig. S16–S19 in the ESI.…”
Section: Resultsmentioning
confidence: 99%
“…85,86 According to the additionally included information for the specic orbitals for each element type, it can be seen that the PDOS of P in the valence and conduction bands are mainly due to p-orbitals, while the major contributor of the interactions is the partially lled d-orbitals of cobalt. In addition, there is overlap between the cobalt 3d-orbitals and phosphorus 3porbitals in the range of À3.1 to À5.3 eV, indicating hybridisation 27 and ensuring stability and strong adsorption of a molecule on the electronically active CoP surface.…”
Section: Electronic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, the great potential of nanoscaled metal phosphides (M x P y ) has been recognized for photovoltaics (InP, Cd 3 P 2 ), [4][5][6] bio-labeling, 7 energy storage, [8][9][10][11] and catalysis. [12][13][14][15][16] While gold is one of the most beloved metals for nanoparticles synthesis due to the wide opportunities that tunable plasmon bands provided for optics, biolabelling, 17 Ramanenhanced spectroscopy, or theragnosis, 18 gold phosphide, on the other hand, has been scarcely investigated at the nanoscale. Bulk Au 2 P 3 is a monoclinic compound.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been made to date to elucidate the surface properties of Ni2P 10 single crystal surfaces, using X-ray photoelectron spectroscopy (XPS) [22,23], scanning 11 tunneling microscopy (STM) [24][25][26][27][28], low-energy electron diffraction (LEED) [24][25][26][27][28][29][30], 12 photoemission electron microscopy (PEEM) [25], photoelectron diffraction [31] and 13 photoemission spectroscopy (PES) [30,[32][33][34][35]. Theoretical calculations using density 14 functional theory (DFT) [11,14,15,[36][37][38] have also played an important role in 15 understanding the catalytic properties of the surface. These studies have indicated that 16 the Ni2P single crystal surface is stabilized by reordering of the P atoms.…”
Section: Introductionmentioning
confidence: 99%